Spatial and Temporal Variation of Aerosol and Water Vapour E ects on Solar Radiation in the Mediterranean Basin during the Last Two Decades - Obregón, Maria Angeles (2020)
This study aims to calculate and analyse the spatial and temporal variation of aerosol optical thickness (AOT) and precipitable water vapour (PWV) and their e ects on solar radiation at the surface in the Mediterranean basin, one of the maritime areas with the largest aerosol loads in the world. For the achievement of this objective, a novel and validated methodology was applied. Satellite data, specifically CERES (Clouds and the Earth’s Radiant Energy System) SYN1deg products during the period 2000–2018, were used. Results show that the spatial distribution of AOT and PWV are closely linked to the spatial distributions of its e ects on solar radiation. These e ects are negative, indicating a reduction of solar radiation reaching the surface due to aerosol and water vapour e ects. This reduction ranges between 2% and 8% for AOT, 11.5% and 15% for PWV and 14% and 20% for the combined e ect. The analysis of the temporal distribution has focused on the detection of trends from their anomalies. This study has contributed to a better understanding of AOT and PWV e ects on solar radiation over the Mediterranean basin, one of the most climatically sensitive regions of the planet, and highlighted the importance of water vapour.